Efektivitas Penggunaan Aplikasi PLN Mobile Pada Bagian Pelayanan Pelanggan Di PLN UP3 Binjai - Annio Indah Lestari Nasution; Ayu Lestari Sitio; Cai Siregar; Leni Lastrian Nahulae (Universitas Katolik Widya Karya Malang, 2023)
PLN (Persero) UP3 Binjai is one of the PLN units responsible for the electricity distribution function. In the electricity business, its position is as an interface with customers. The aim of this research is to determine the effectiveness of using the PLN Mobile application in the customer service section at PLN UP3 Binjai. In collecting research data, a qualitative method was used consisting of interviews and observations as well as literature review, interviews were conducted to PLN employees in the customer service department and PLN mobile users. The results of the research are that the PLN Mobile Application is quite good and very useful for UP3 Binjai customers to fulfill electricity needs, complaints and grievances, however, socialization is not yet evenly distributed so that there are still PLN customers UP3 Binjai who have not used the PLN Mobile application. Apart from that, the PLN Mobile application also has a positive impact on both customers and PLN employees because it will be more effective and save time and energy for both customers and employees in resolving customer complaints.